High Level of Uromodulin Increases the Risk of Hypertension: A Mendelian Randomization Study - You, Ruilian; Chen, Lanlan; Xu, Lubin; Zhang, Dingding; Li, Haitao; Shi, Xiaoxiao; Zheng, Yali; Chen, Limeng (Frontiers in Cardiovascular Medicine, 2021)
Background: The association of uromodulin and hypertension was observed in the clinical study, but not proved a causal relationship. We conducted two-sample Mendelian randomization(MR) analysis to investigate the causal relationship between uromodulin and blood pressure. Methods: We selected SNPs related to urinary uromodulin(uUMOD) and serum uromodulin(sUMOD) from a large Genome-Wide Association Studies (GWAS) meta-analysis study and research in Pubmed. Six datasets based on the UKbibank and the International Consortium for Blood Pressure(ICBP) served as outcomes with a large sample of hypertension(n=46,188), systolic blood pressure (SBP, n=1,194,020), and diastolic blood pressure(DBP, n=1,194,020). Inverse variance weighted(IVW) method was performed in uUMOD MR-analysis, while methods of IVW, MR-Egger, Weighted median, and MR-PRESSO were utilized on sUMOD MR-analysis. Results: MR analysis showed the odds ratio(OR) of the uUMOD to hypertension ("ukb-b-14057" and "ukb-b-14177") is 1.04(95% Confidence Interval (CI), 1.03-1.04, p-value＜0.001), The effect sizes of the uUMOD to SBP are 1.10(SE=0.25,p-value=8.92E-06) and 0.03(SE=0.01,p-value=2.70E-04) in "ieu-b-38" and "ukb-b-20175" respectively. The β coefficient of the uUMOD to DBP is 0.88(SE=0.19, p-value=4.38E-06) in "ieu-b-39" and 0.05(SE=0.01, p-value=2.13E-10) in "ukb-b-7992". As for the sUMOD, the OR of the hypertension ("ukb-b-14057" and "ukb-b-14177") is 1.01(95%CI 1.01-1.02, all p-value＜0.001). The β coefficient of the SBP is 0.37(SE=0.07, p-value=1.26E-07) in "ieu-b-38" and 0.01(SE=0.003, p-value=1.04E-04) in "ukb-b-20175". The sUMOD is casually associated with elevated DBP("ieu-b-39":β=0.313, SE=0.050, p-value=3.43E-10; "ukb-b-7992": β=0.018, SE=0.003, p-value=8.41E-09). Conclusion: Our results indicated that high urinary and serum uromodulin levels are detrimental to elevate blood pressure, and served as a causal risk factor for hypertension.